Arachidonic acid suppresses lung cancer cell growth and modulates lipid metabolism and the ERK/PPARγ signaling pathway - Lin Wang; Lanlan Wei; Xueling Chen; Jiali Xiong (Lipids in Health and Disease)
Abstract Lung cancer remains the leading cause of cancer-related mortality worldwide, necessitating the development of new treatment strategies. Arachidonic acid (ARA), a polyunsaturated fatty acid, shows promise in cancer therapy due to its potential anti-tumor effects, although its role in lung cancer remains unclear. This study investigated the effects and underlying mechanism of ARA on A549 and NCI-H1299 lung cancer cells. In vitro assays were used to assess cell viability, apoptosis, colony formation, lipid droplet formation, and changes in cellular lipid content. ARA dose-dependently suppressed cell viability, facilitated apoptosis, and suppressed colony formation in both lung cancer cell lines. Network pharmacology analysis was performed to identify potential gene targets and pathways, uncovering 61 overlapping genes between ARA and lung cancer-related targets, with mitogen-activated protein kinase 1 (MAPK1) emerging as a key gene. Enrichment analyses suggested that the effects of ARA might be mediated through lipid metabolism and the extracellular signal-regulated kinase (ERK)/peroxisome proliferator-activated receptor gamma (PPARγ) signaling pathway. In both lung cancer cell lines, ARA treatment inhibited lipid droplet formation and decreased the cellular lipids. Immunoblotting further confirmed that ARA treatment significantly increased ERK phosphorylation while reducing PPARγ and fatty acid synthase (FASN) protein levels. In vitro experiments using GW9662, a PPARγ antagonist, confirmed that inhibiting lipid droplet formation impairs lung cancer cell viability and promotes apoptosis. Furthermore, in vivo experiments demonstrated that ARA significantly reduced tumor size and weight in a lung cancer xenograft model, further validating its anti-tumor effects. The potential of ARA as a therapeutic agent for lung cancer might involve lipid metabolism and relevant signaling pathways. A future study exploring the full therapeutic potential of ARA and underlying mechanisms in lung cancer is needed.